Purification and Initial Characterization of 3-Hydroxybenzoate 6-Hydroxylase From a Halophilic Martelella Strain AD-3 - Chen, Xin; Tang, Hongzhi; Liu, Yongdi; Xu, Ping; Xue, Yong; Lin, Kuangfei; Cui, Changzheng (Frontiers in Microbiology, 2018)
3-Hydroxybenzoate 6-hydroxylase, an NADH-dependent flavoprotein, can convert 3-hydroxybenzoate which is an important intermediate in the biodegradation of many aromatic hydrocarbons. 3-Hydroxybenzoate is metabolized by entering the TCA cycle through the gentisate pathway. We found a putative 3HB6H gene from a cluster that potentially encodes for gentisic acid degradation from a halophilic Martelella sp. strain AD-3. The corresponding protein was expressed with an N-terminal His-tag and purified by Ni2+-nitrilotriacetic acid affinity chromatography. The protein showed an overexpressed band of about 46 kDa by SDS–PAGE, and it was also proven that the enzyme contains FAD by absorption spectroscopy and HPLC analysis. The optimal activity of 3HB6H from strain AD-3 was observed in phosphate buffer (pH 8.0) at 37°C without salinity (NaCl) and metal salts. The Km values of 3-hydroxybenzoate 6-hydroxylase were determined to be 72.6 ± 10.1 μM and 104.1 ± 18.2 μM for 400 μM NADH and 3-hydroxybenzoate, respectively. Site-directed mutagenesis showed that residues 305, 306 and 308 are important for FAD binding. In addition, we found that Tyr221 and Gln305 of 3HB6H from strain AD-3 are involved in substrate binding.